Controlling the α/γ‐Reactivity of Vinylogous Ketone Enolates in Organocatalytic Enantioselective Michael Reactions. (20th June 2017) - Iriarte, Igor; Olaizola, Olatz; Vera, Silvia; Gamboa, Iñaki; Oiarbide, Mikel; Palomo, Claudio
Abstract: The first regio‐, diastereo‐, and enantioselective direct Michael reaction of β, γ‐unsaturated ketones with nitroolefins is enabled by Brønsted base/hydrogen‐bonding bifunctional catalysis. A squaramide‐substituted tertiary amine catalyzes the reaction of a broad range of β, γ‐unsaturated ketones to proceed at the α‐site exclusively, giving rise to adducts with two consecutive tertiary carbon stereocenters in diastereomeric ratios of up to >20:1 and enantioselectivities generally in the 90–98 % ee range.